ELA, promissory notes and all that: The fiscal costs of Anglo Irish Bank - Karl Whelan (University College Dublin, UCD School of Economics, 2012)
This is a briefing paper the author distributed to the Irish parliamentary committee responsible for finance and public expenditure. It describes the balance sheet of Irish Bank Resolution Corporation, the organisation that was formed by combining Anglo Irish Bank and Irish Nationwide Buildings Society. The nature of the long-run cost to the Irish state of taking over the liabilities of these institutions is outlined and suggestions are made for reducing these costs.
Keywords: 330